Prints as agents of global exchange 1500-1800 - Madar, Heather (Visual and material culture, 1300-1700, 2021)
Cover -- Table of Contents -- Introduction -- Heather Madar -- 1. Concealing and Revealing the Female Body in European Prints and Mughal Paintings -- Saleema Waraich -- 2. The Sultan's Face Looks East and West: European Prints and Ottoman Sultan Portraiture -- Heather Madar -- .3 From Europe to Persia and Back Again: Border-Crossing Prints and the Asymmetries of Early Modern Cultural Encounter -- Kristel Smentek -- 4. The Dissemination of Western European Prints Eastward: The Armenian Case -- Sylvie L. Merian -- 5. The Catholic Reformation and Japanese Hidden Christians: Books as Historical Ties -- Yoshimi Orii -- 6 .(Re)framing the Virgin of Guadalupe: The Concurrence of Early Modern Prints and Colonial Devotions in Creating the Virgin -- Raphaèle Preisinger -- 7. Hidden Resemblances: Re-contextualized and Re-framed: Diego de Valadés' Cross Cultural Exchange -- Linda Báez and Emilie Carreón -- 8. The Practice of Art: Auxiliary Plastic Models and Prints in Italy, Spain, and Peru -- Alexandre Ragazzi -- 9. Ink and Feathers: Prints, Printed Books, and Mexican Featherwork -- Corinna T. Gallori -- Index -- List of illustrations -- 1 Concealing and Revealing the Female Body in EuropeanPrints and Mughal Paintings -- Figure 1 A Celestial Woman Attendant with a Vina (Stringed Instrument). Artist/maker unknown. 956-973, Sandstone, 25 1/8 × 10 1/2 × 7 1/4 inches (63.8 × 26.7 × 18.4 cm). Philadelphia Museum of Art, Purchased from the Stella Kramrisch Collection with funds -- Figure 2 Pietas Regia, the second title page from the first volume of Plantiin Biblia Sacra (also known as the Polyglot Bible). Printed by Christopher Plantiin in Antwerp between 1568-72. Newberry Digital Collections (Newberry Library).